Carbon/Nitrogen Status of Soils under some Plant Communities of Churu, Rajasthan - Sharma, B. M. (Indian Forester, 1967)
Carbon/Nitrogen ratio of soils with respect to certain communities of Churu in Rajasthan has been discussed in the paper. Thirty soil samples each from the surface and 15 cm depth from sandy plains, dunes and depressions were examined for pH, organic carbon and nitrogen content. The Investigation reveals that the soils are alkaline with organic carbon ranging from 0.06 to 0.81 per cent and nitrogen from 0.003 to 0.336 per cent. The Carbon/Nitrogen ratio is quite narrow (0.57 to 4.54) in Aerva-Leptadenia and Cenchrus-Laptadenia communities. A wider ratio (4.16 to 64.28) was observed in Prosopisna dactylactenium community. However, in most of the cases the ratio varied from 0.31 to 11.9.